Immune checkpoint inhibitors in renal cell carcinoma - Ross, Kirsty (Clin Sci (Lond), 2017)
The immune system has long been known to play a critical role in the body’s defence against cancer, and there have been multiple attempts to harness it for therapeutic gain. Renal cancer was, historically, one of a small number of tumour types where immune manipulation had been shown to be effective. The current generation of immune checkpoint inhibitors are rapidly entering into routine clinical practice in the management of a number of tumour types, including renal cancer, where one drug, nivolumab, an anti-programmed death-1 (PD-1) monoclonal antibody (mAb), is licensed for patients who have progressed on prior systemic treatment. Ongoing trials aim to maximize the benefits that can be gained from this new class of drug by exploring optimal timing in the natural course of the disease as well as combinations with other checkpoint inhibitors and drugs from different classes.